GENDER DIFFERENCES: DIGITAL PAYMENT AND FINANCIAL LITERACY ON CONSUMPTIVE BEHAVIOR IN SOCIETY - Apriliana Wahyu Pratiwi; Arie Setyo Dwi Purnomo; Prasetyo Nugroho (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective – By looking at differences based on gender, this research examines how digital payment and financial literacy influence consumptive behavior. In addition, this research also investigates how modern digitalization will influence individual overconsumption patterns.Design/Methodology/Approach – Partial Least Square (PLS SEM), a quantitative approach, and the purposive sampling method were applied in this research. SmartPLS 4.0 software was used to process this research data from 100 respondents from the Pamekasan community.Findings – According to this research, the use of digital payment tends to encourage an increase in excessive consumption habits, but financial literacy has an adverse correlation with this behavior. In addition, there are significant differences between genders in terms of the impact of digital payment on consumptive behavior, but the same differences are not found in terms of the influence of financial literacy.Conclusion and Implications – This research enriches knowledge about consumptive behavior for people who are very attached to financial technology such as digital payment. This research also shows that every individual needs financial literacy to control consumptive behavior. Keywords: Digital Payment, Financial Literacy, Consumptive Behavior, Gender